The Effectiveness of the Pelita Hati Library as a Means of Promoting Community Literacy in Nanggerangjaya Village - Dedeh Ermawati; Siti Khumayah (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to analyze the effectiveness of the management of the Pelita Hati Library as a means of promoting public literacy in NanggerangJaya Village, Mandirancan Subdistrict, Kuningan Regency, as well as to identify the factors that support and hinder such management. This study employs a qualitative approach using descriptive methods. Informants were selected through purposive sampling and consisted of the Village Head of NanggerangJaya and the Manager of the Pelita Hati Library. Data collection was conducted through interviews, observations, and documentation, and the data were analyzed using the Miles and Huberman interactive analysis model based on Richard M. Steers’ theory of organizational effectiveness, which encompasses four dimensions: goal attainment, integration, adaptation, and sustainability. The research results indicate that, in terms of goal achievement, the library has organized a number of literacy programs, community participation remains suboptimal due to relatively low reading interest. In terms of integration, there is good communication and cooperation between the village government, the library manager, and the Posyandu Remaja (Youth Health Post) activities. In terms of adaptation, the library still faces constraints related to human resources, space, and budget, yet it continues to strive to maintain its literacy activities. Regarding sustainability, there is a commitment from the village government and library administrators to ensure the library’ continued operation through the establishment of a management board and the allocation of funds. Overall, the Pelita Hati Library has been quite succes activities, but it still requires strengthening of human resources, improvement of facilities, and community participation so that the library’s function as a literacy resource can be optimal in the village.